2018
DOI: 10.1093/icesjms/fsx241
|View full text |Cite
|
Sign up to set email alerts
|

Ocean destratification and fish evacuation caused by a Mid-Atlantic tropical storm

Abstract: Tropical and extratropical storms commonly occur in the Northwest Atlantic Ocean, sometimes causing catastrophic losses to coastal fisheries. Still, their influence on fish movements and range shifts is poorly known. We coupled biotelemetry observations of black sea bass in the U.S. Mid-Atlantic Bight with numerical modelling of the coastal ocean to evaluate the influence of Hermine (3–8 September 2016) on cold pool thermal destratification and fish evacuation. Spring through fall, black sea bass is a sedentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Our study found that storms in the US Mid-Atlantic Bight caused sea surface temperature anomalies to vary, as was expected based on the mixing of the stratified water column with cooler bottom water, thus lowering the surface temperature, as found in other studies 14 . While lower water temperatures are unlikely to have directly affected the dolphins' behavior, their ectothermic prey species are influenced by these changes 14,39 . The resulting changes in prey distribution may have indirectly influenced dolphin movements and foraging.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our study found that storms in the US Mid-Atlantic Bight caused sea surface temperature anomalies to vary, as was expected based on the mixing of the stratified water column with cooler bottom water, thus lowering the surface temperature, as found in other studies 14 . While lower water temperatures are unlikely to have directly affected the dolphins' behavior, their ectothermic prey species are influenced by these changes 14,39 . The resulting changes in prey distribution may have indirectly influenced dolphin movements and foraging.…”
Section: Discussionsupporting
confidence: 89%
“…During Tropical Storms Jose and Maria, intense wave action caused gray triggerfish (Balistes capriscus) in North Carolina to increase their emigration rates 44 . Concurrent research in our study region found that black sea bass (Centropristis striata) evacuated the region as a result of Tropical Storm Hermine in 2016 14 . Water column mixing and changing bottom temperatures initiated a migration of 40% of tagged black sea bass and caused reduced activity rates by those that remained 14 .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…After the onset of strati cation, ΔT ranged from 0.8-12.9 °C at the nearshore site and 1.7-17.4 °C at the mid-shelf site until the Cold Pool rapidly collapsed from September 7-10; stronger thermal strati cation consistently occurred at the deeper mid-shelf site as compared to the nearshore site. Acute periods of partial-to-complete destrati cation of nearshore waters are often associated with large wind events or tropical storms [21], and were observed on May 16-19, June 2-4, July 5-9, and August 19-24 where ΔT decreased by 3.5-8.7 °C ΔT over the course of several hours to several days.…”
Section: Mid-atlantic Cold Poolmentioning
confidence: 99%